An assessment of occupational health and safety uptake among artisanal miners in Ghana. - Stephens, Daniel Kofi (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment of the Requirement for the Degree Of Master of Business Administration (Strategic Management and Management Consulting Option).